Safety and efficacy of 3‐phytase FSF10000 as a feed additive for chickens for fattening or reared for laying, laying hens and minor poultry species. (15th January 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The additive 3‐phytase FSF10000 is a solid product that contains a 3‐phytase produced by a genetically modified strain of Komagataella phaffii . A liquid formulation of the additive has been previously assessed by the EFSA Panel on Additives and Products of Substances used in Animal Feed (FEEDAP) and is currently authorised as a feed additive for poultry species. The applicant requested for the use of this new formulation of the additive in chickens for fattening or reared for laying/breeding, laying hens and minor poultry species for fattening or reared for laying/breeding. Therefore, in this assessment, the new formulation of the product has been characterised and its safety and efficacy has been evaluated. The production strain and its DNA were not detected in the solid formulation. Therefore, the additive poses no concerns with regard to the genetic modification of the production strain. The Panel concluded, based on studies conducted with the liquid formulation, that the additive 3‐phytase FSF10000 is safe for the target species at 1, 000 FTU/kg feed. Also, considering the production strain and composition of the final additive the Panel concluded that the additive raises no safety concerns for the consumer of products obtained from animals fed the additive or for the environment. The additive 3‐phytase FSF10000 is not irritant to skin and eyes but it is a skin dermal sensitiser and is considered to be a respiratory sensitiser. Based on studies conducted with the liquid formulation, the Panel concluded that the 3‐phytase FSF10000 has a potential to be efficacious in chickens for fattening or reared for laying and in minor poultry species for fattening or reared for laying/breeding at 500 FTU/kg feed and in laying hens at 1, 000 FTU/kg feed.